Biotransformation of Platycosides, Saponins from Balloon Flower Root, into Bioactive Deglycosylated Platycosides - Kyung-Chul Shin; Deok-Kun Oh (MDPI AG, 2023)
Platycosides, saponins from balloon flower root (Platycodi radix), have diverse health benefits, such as antioxidant, anti-inflammatory, anti-tussive, anti-cancer, anti-obesity, anti-diabetes, and whitening activities. Deglycosylated platycosides, which show greater biological effects than glycosylated platycosides, are produced by the hydrolysis of glycoside moieties in glycosylated platycosides. In this review, platycosides are classified according to the chemical structures of the aglycone sapogenins and also divided into natural platycosides, including major, minor, and rare platycosides, depending on the content in Platycodi radix extract and biotransformed platycosides. The biological activities of platycosides are summarized and methods for deglycosylation of saponins, including physical, chemical, and biological methods, are introduced. The biotransformation of glycosylated platycosides into deglycosylated platycosides was described based on the hydrolytic pathways of glycosides, substrate specificity of glycosidases, and specific productivities of deglycosylated platycosides. Methods for producing diverse and/or new deglycosylated platycosides are also proposed.